Modern society transformation and contemporary social challenges: Toward an integrated Qur'anic and Hadith perspective - Faelalika Putri Herhan; Amirul Bakhri (PT Bina Perfidia Akademia, 2026)
Modern society transformation has generated increasingly complex social challenges, yet previous studies have generally examined digital ethics, mental health, the digital economy, and environmental issues separately without offering an integrated conceptual framework based on the Qur'an and Hadith. This study aims to analyze the perspectives of the Qur'an and Hadith in addressing contemporary social challenges by synthesizing theories of modern society transformation with Islamic ethical values. This research employed a qualitative library research design using a conceptual approach and thematic analysis of relevant scholarly literature and Islamic sources. The findings indicate that the principles of tabayyun and amānah, spiritual well-being, muʿāmalah, and khalīfah fī al-arḍ constitute an integrated ethical framework for addressing digital ethics, mental health, the digital economy, and environmental issues. This study contributes by proposing a conceptual model that reinforces the relevance of Islamic teachings as an ethical foundation for building a modern society that is ethical, just, and sustainable. Abstrak Transformasi masyarakat modern telah melahirkan berbagai tantangan sosial yang semakin kompleks. Namun, penelitian terdahulu umumnya masih membahas isu etika digital, kesehatan mental, ekonomi digital, dan lingkungan secara terpisah sehingga belum menawarkan kerangka konseptual yang mengintegrasikan perspektif Al-Qur'an dan Hadis. Penelitian ini bertujuan menganalisis perspektif Al-Qur'an dan Hadis dalam merespons tantangan sosial kontemporer melalui sintesis antara transformasi masyarakat modern dan nilai-nilai etika Islam. Penelitian ini menggunakan pendekatan kualitatif dengan metode library research, conceptual approach, serta thematic analysis terhadap literatur ilmiah dan sumber-sumber keislaman yang relevan. Hasil penelitian menunjukkan bahwa prinsip tabayyun dan amānah, spiritual well-being, muʿāmalah, serta khalīfah fī al-arḍ membentuk suatu kerangka etik yang terintegrasi dalam merespons tantangan etika digital, kesehatan mental, ekonomi digital, dan isu lingkungan. Penelitian ini berkontribusi dengan menawarkan model konseptual yang memperkuat relevansi ajaran Islam sebagai landasan etik bagi pembangunan masyarakat modern yang etis, adil, dan berkelanjutan.